THE EFFECT OF COMPANY SIZE AND INVESTMENT OPPORTUNITY SET ON AUDIT REPORT LAG WITH FINANCIAL DISTRESS AS A MODERATING VARIABLE: (Empirical Study of Infrastructure, Utilities and Transportation Sector Companies in 2019-2021) - Febby Agustini Armeliya; Zulfa Rosharlianti (Transpublika Publisher, 2023)
In the contemporary business landscape, financial reporting and auditing play a crucial role in maintaining transparency, accountability, and investor confidence within organizations. The timing of audit reports, commonly referred to as audit report lag, is an important aspect of financial reporting that reflects the efficiency and effectiveness of an organization's financial reporting process. Several factors can influence audit report lag, including the size of the firm, the presence of investment opportunities, and financial difficulties that a company might face. This study aims to empirically investigate the influence of firm size and investment opportunity sets on audit report lag, and whether financial difficulties can moderate the impact of company size and investment opportunity sets on the delay in audit reports. The research focuses on the infrastructure, utilities, and transportation sectors listed on the Indonesia Stock Exchange for the period 2019 to 2021. Employing a quantitative research approach, this study utilizes secondary data collection techniques, specifically documentation, and involves a sample of 24 companies. The findings reveal that Company Size significantly affects Audit Report Lag, while Investment Opportunity Set does not have a discernible impact on Audit Report Lag. Additionally, the study demonstrates that Financial Distress does not act as a moderating factor in the relationship between Company Size and Audit Report Lag, nor between Investment Opportunity Set and Audit Report Lag. When considered together, Company Size and Investment Opportunity Set concurrently exhibit a significant influence on Audit Report Lag.